Stump appendicitis: an uncommon dilemma - Pereira, Chirag; Tauro, Leo F. (International Surgery Journal, 2020)
Stump appendicitis is one of the rare delayed complications post appendectomy with a reported incidence of 1 in 50,000 cases. Stump appendicitis can present as a diagnostic dilemma if the treating clinician is unfamiliar with this rare clinical entity. The purpose of this paper is to review current data on stump appendicitis and analyse published cases.